2017
DOI: 10.1016/j.ijdevneu.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

A prenatal nicotine exposure mouse model of methylphenidate responsive ADHD‐associated cognitive phenotypes

Abstract: Prenatal exposure to nicotine via cigarette smoke or other forms of tobacco use is a significant environmental risk factor for attention deficit hyperactivity disorder (ADHD). The neurobiological mechanisms underlying the link between prenatal nicotine exposure (PNE) and ADHD are not well understood. Animal models, especially rodent models, are beginning to bridge this gap in knowledge. Although ADHD is characterized by hyperactivity, inattention, impulsivity and working memory deficits, the majority of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 74 publications
4
65
2
Order By: Relevance
“…Preclinical studies [ 4 , 5 , 12 16 ] and clinical studies [ 3 , 17 20 ] show that prenatal nicotine exposure produces significant attention deficits. Therefore, we used an object-based attention test [ 13 , 21 , 22 ] to examine the effects of paternal nicotine exposure on attention in the F1 mice. Paternal treatment produced a significant main effect on attention (two-way ANOVA; treatment: F [1, 35] = 9.23; p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Preclinical studies [ 4 , 5 , 12 16 ] and clinical studies [ 3 , 17 20 ] show that prenatal nicotine exposure produces significant attention deficits. Therefore, we used an object-based attention test [ 13 , 21 , 22 ] to examine the effects of paternal nicotine exposure on attention in the F1 mice. Paternal treatment produced a significant main effect on attention (two-way ANOVA; treatment: F [1, 35] = 9.23; p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Working memory and cognitive flexibility are components of executive function [ 23 27 ] impacted by drug exposure [ 28 , 29 ]. We have previously reported that nicotine or cocaine exposure of pregnant mice impairs working memory and cognitive flexibility in the offspring [ 22 , 30 ]. We analyzed spatial working memory in F1 mice using the Y-maze.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are in agreement with previous nicotine work and suggest a key area of risk for BaP exposure. Fetal nicotine exposure has been previously associated with poor rodent attention tasks, such as the 5-choice serial response time task (Schneider, Bizarro, Asherson, & Stolerman, 2012;Schneider et al, 2011) and the object-based attention test (Alkam et al, 2013;Zhu et al, 2017). This particular attention task had not previously been found to be sensitive to prenatal nicotine effects when used by Hall et al (2016) although that data set did find deficits in novel object recognition, which is believed to rely on another form of attention.…”
Section: Discussionmentioning
confidence: 99%